Chronic Appendicitis as a Differential Diagnosis of Chronic Abdominal Pain. Clinical Case - Montero-Sánchez, Olga Nidia; Pesqueira-Valerio, María Gabriela; Trujillo-Cedillo, Octavio Javier; Lugo-Guevara, Yadira Irasema; Falcón-Cancino, Luis Arturo; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2024)
Chronic appendicitis represents a rare surgical pathological entity, which is also tricky for first-contact physicians to consider as a differential diagnosis when faced with a patient with abdominal pain. There are currently well-described diagnostic criteria for it. The case of a 24-year-old female patient with no significant medical history presented with a picture of abdominal pain over three weeks of evolution. Moreover, diagnosed by contrast-enhanced computerized axial tomography with appendicitis, an open appendectomy was performed, and the histological examination confirmed the diagnosis of chronic appendicitis associated with fecalith obstruction.